Development of New Generation Electrodes for Registration of Heart Bioelectric Potentials - Ye. V. Lemeshko; S. N. Vasukevich; S. V. Goubkin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
When conducting electrophysiological studies, electrodes are used to register bioelectrical signals, the correct choice and use of which determine the reliability and diagnostic significance of the data obtained. Recording an electrocardiogram is a standard procedure in medicine, but its monitoring is often limited to 24 hours.This is due to the limited performance of the electrodes. The properties of the skin/electrode interface determine the performance of medical equipment. Therefore, the surface conditions and the composition of the material from which the electrode is made should comply with the requirements of the electrocardiogram recording device. It is important to implement fast transmission of a useful signal with low losses and without artifacts. Modern electrodes using Ag/AgCl have a limited-service life, since their dehydration and surface degradation lead to the formation of various artifacts on the electrocardiogram record. Alternative – dry flexible electrodes. Such electrodes can be based on carbon materials (reduced graphene oxide or a diamond-like coating) on a plastic (film) substrate. The emphasis of modern research is aimed at carrying out work on the development of dry electrodes, which would provide an opportunity to carry out high-quality long-term registration of electrocardiosignals without gels and adhesives.